2007
DOI: 10.1111/j.1365-2966.2007.12189.x
|View full text |Cite
|
Sign up to set email alerts
|

The different physical mechanisms that drive the star formation histories of giant and dwarf galaxies

Abstract: We present an analysis of star formation and nuclear activity in galaxies as a function of both luminosity and environment in the fourth data release of the Sloan Digital Sky Survey. Using a sample of 27 753 galaxies in the redshift range 0.005 < z < 0.037 that is ≳90 per cent complete to Mr=−18.0, we find that the Hα equivalent width, EW(Hα), distribution is strongly bimodal, allowing galaxies to be robustly separated into passively evolving and star‐forming populations about a value EW(Hα) = 2Å. In high‐dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
158
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(186 citation statements)
references
References 206 publications
(349 reference statements)
22
158
5
1
Order By: Relevance
“…All this suggests that being a satellite in the vicinity of a massive central is a necessary condition to create a quiescent dwarf galaxy, in agreement with recent results (Haines et al 2007(Haines et al , 2008Weisz et al 2011;Geha et al 2012). Internal mechanisms -such as gas consumption via star formation or feedback effects -appear to be insufficient to completely cease the star formation activity in dwarf galaxies.…”
Section: Environmentsupporting
confidence: 77%
“…All this suggests that being a satellite in the vicinity of a massive central is a necessary condition to create a quiescent dwarf galaxy, in agreement with recent results (Haines et al 2007(Haines et al , 2008Weisz et al 2011;Geha et al 2012). Internal mechanisms -such as gas consumption via star formation or feedback effects -appear to be insufficient to completely cease the star formation activity in dwarf galaxies.…”
Section: Environmentsupporting
confidence: 77%
“…A higher fraction of passive sources are found in group and pair environments than are isolated -the passive peak is significantly larger for group and pair galaxies than for the isolated galaxies. This highlights the well-known trend of galaxy SF in group environments; for example, see Haines et al (2007), Haines, Gargiulo & Merluzzi (2008), Peng et al (2010), Mahajan, Haines & Raychaudhury (2010) and Mahajan et al (2015).…”
Section: E F I N I N G S Ta R -F O R M I N G / Pa S S I V E S Y S Tmentioning
confidence: 99%
“…Similarly, the morphology-density relation is very strong for low-mass galaxies (e.g., Binggeli et al 1990). It has also been found that the bulk of dwarf galaxies in galaxy groups and clusters are passively evolving, while, as the local density decreases, the fraction of passively evolving dwarfs drops rapidly, reaching zero in the rarefied field (e.g., Haines et al 2007).…”
Section: Introductionmentioning
confidence: 99%